The Effect of Taxation Knowledge and Tax Sanctions on Compliance of MSME Taxpayers in Bandung City - Ghifari, Farhan Fadil (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
The tax industry generates the majority of Indonesia's state revenue. In the evolution of the Indonesian state, taxes are a crucial tool. For this reason, it is crucial that taxpayers fulfill their tax responsibilities. Strong state revenue will also come from strong compliance. But the fast rise of micro, small, and medium-sized businesses also needs attention because they have a huge opportunity to bring in money for the state. In order for these micro, small, and medium-sized businesses (MSMEs) to pay their taxes, the government should help and guide them. The point of this study is to look into how tax fines and tax compliance affect people in the Bandung City area following the law. Through surveys, businesses that were classified as micro, small, or medium were called. The businesses were picked at chance. The author got information from 153 different people. After that, the results were put through a number of tests, such as validity and reliability studies. After that, regression and normal assumption tests were done with SPSS version 27. What the study found shows is how important tax fines and tax rule knowledge are for people to follow the rules. Also, the sum of tax fines and tax information changes how well people follow the rules. The writer says the government will help and give more advice to small, small, and medium-sized businesses in and around Bandung City. Their plan is to share the tax money to make this happen. This will make people more likely to pay their taxes, which will help the state get more money. The study's results show that tax understanding and tax penalties affect how well people in the Bandung City area pay their taxes. 54.9% of the people have power.